Measurement of Consumer Satisfaction of Product Quality Using the Customer Satisfaction Index Method and Importance Performance Analysis: Pengukuran Kepuasan Konsumen Terhadap Kualitas Produk Menggunakan Metode Customer Satisfaction Index Dan Importance Perfomance Analysis - Wardana, Acmad Bayu; Sumarmi, Wiwik (Indonesian Journal of Innovation Studies, 2019)
Satisfaction of Consumer represent storey level satisfaction of consumer after what in processing in data processing. This research use glorious partner at CV case study of collection. This research aim to to know storey level satisfaction of consumer to quality of Glorious LIMITED PARTNER, CV Partner product of Collection with CSI method and which need to be improve repaired and developed any kind of according to IPA method. This Research is executed to Glorious LIMITED PARTNER, CV Partner cutomer client of Collection which have transacted more than one year. from this Research represent research of quantitative diskriptif with research device method. Amount of research sampel 100 Glorious LIMITED PARTNER, CV Partner cutomer client of Collection that is. Data analysis use Importance Performance Analysis ( IPA) And Customer Satifaction Index ( CSI). Result of research show attribute which need to be paid attention Glorious LIMITED PARTNER, CV Partner of Collection to fulfill satisfaction of its consumer is I kuadran that is Product specification ( 7), Price Product According to Quality ( 8), Product Company Have Positive Image In Company ( 18) Given By Company.